Design of a Cashless Vending Machine System for the Distribution and Conservation of Traditional Herbal Medicine - Monika Faswia Fahmi; Deni Tri Laksono; Muhammad Arya Rangga Waskita Wicaksono (Jurusan Teknik Elektro Universitas Trunojoyo Madura, 2025)
Indonesia, as a center of biodiversity, plays a significant role in preserving various plant species, including approximately 28,000 plant varieties and 7,500 medicinal plant species, representing 10% of the global total. Indonesians have long relied on traditional herbal remedies derived from wild plants, with jamu being one of the most prominent products. However, the market penetration and accessibility of traditional jamu remain limited. This research proposes the implementation of a vending machine with a cashless payment system to improve accessibility and promote the preservation of traditional jamu. The vending machine provides six jamu variants and three water temperature options, utilizing a cashless payment system integrated with an ESP-32 and Arduino MEGA 2560 microcontroller. The system incorporates the Midtrans payment gateway with a dedicated website to support seamless cashless transactions. Test results show that the vending machine dispenses jamu with an average weight of 219.81 g, yielding an error margin of 1.18% from the 220 g setpoint. The average brewing time is 93.7 seconds, with water temperature aligning with user preferences. Cashless payment testing achieved a 100% success rate, demonstrating the system’s effectiveness.